Does Physical Exercise Enhance the Immune Response after Vaccination? A Systematic Review for Clinical Indications of COVID-19 Vaccine - Barni, Luca; Carrasco-Vega, Elio; Olivieri, Matteo; Galán Mercant, Alejandro; Guiducci, Serena; Picariello, Felice; González-Sánchez, Manuel (MPDI, 2023)
Background: Stimulating protective immunity with vaccines appears to be the most promising option for providing widespread moderate to high protection against COVID-19 in people over the age of 18. Regular exercise improves the immune response, transmitting possible benefits against virus infections. The aim of this review is to study the effects of physical activity on vaccine injections, helping to develop new recommendations for COVID-19 vaccination campaigns. Methods: A comprehensive review of the existing literature was undertaken using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The internal quality of the studies was assessed according to the Physiotherapy Evidence Database (PEDro) scale. The outcomes analyzed were antibody titer, the level of lymphocytes CD4, CD8, InterLeukin 6 (IL6), leukocytes level, the visual analogue scale (VAS) for overall pain rating, arm and forearm circumferences and volume of oxygen (VO2) peak. Results: Fourteen articles were selected for the analysis. The majority of studies were randomized controlled trials (RCT) (n = 8) and controlled trials (CT) (n = 6). According to PEDro, the ‘fair’ category (n = 7) was the most represented, followed by ‘good’ (n = 6) and ‘excellent’ (n = 1). Physical training showed a positive effect on antibody titers of the vaccine; yet, different variables seem to influence antibody titers: higher new vs. old antigen in the vaccine, higher in younger vs. older individuals, and higher in females vs. males. After exercise, when analyzing variables of direct response to the vaccine, such as the amount of CD4, IL-6 and leukocytes, higher levels were observed in the patients who performed physical exercise compared to the control group. In the same way, better results were observed in physiological variables such as VO2 and limb circumferences, or subjective variables such as pain, which showed better results than the control group. [...]
Keywords: Vacunas; Ejercicio físico; Vaccination; Immune response; Physical exercise